2011
DOI: 10.1089/scd.2010.0145
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Mesenchymal Stem Cells Derived from Dental Pulp and Dental Follicle are Susceptible to Activation by Toll-Like Receptor Agonists

Abstract: Adult mesenchymal stem cells (MSCs) have recently become a potent tool in regenerative medicine. Due to certain shortcomings of obtaining bone marrow MSCs, alternate sources of MSCs have been sought. In this work, we studied MSCs from dental pulp (DP-MSCs) and dental follicle (DF-MSCs), isolated from the same tooth/donor, to define differences in their phenotypic properties, differentiation potential, and immunomodulatory activities. Both cell types showed colony-forming ability and expressed typical MSCs mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 58 publications
7
134
1
3
Order By: Relevance
“…This low expression of STRO-1 is in agreement with other reports in PDLSCs, 27 PDL cells, 28 dental pulp and dental follicle stem cells. 29 After exposure to bacterial toxin, on average 0.71% of PDLSCs remained positive for STRO-1. Stem cell markers expression showed that there was no significant difference in exposed versus non-exposed cells, however it is important to highlight the distinct behavior of each PDLSC population.…”
Section: Discussionmentioning
confidence: 95%
“…This low expression of STRO-1 is in agreement with other reports in PDLSCs, 27 PDL cells, 28 dental pulp and dental follicle stem cells. 29 After exposure to bacterial toxin, on average 0.71% of PDLSCs remained positive for STRO-1. Stem cell markers expression showed that there was no significant difference in exposed versus non-exposed cells, however it is important to highlight the distinct behavior of each PDLSC population.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8]17,18 DPSCs are identified by their negative expression of hematopoietic antigens (e.g., CD45, CD34, CD14), and positive expression of CD90, CD29, CD73, CD105, CD44 and STRO-1. 19,20 Easy obtained potential with minimum pain & morbidity make human DPSCs as a valuable source of MSCs compared to the ordinary sources, such as bone marrow mesenchymal stem cells 21 . In general, DPSCs have been isolated by either outgrowth method, i.e., migration of stem cells from pulp tissue explants (DPSC-OG) [22][23][24] , and/or by enzymatic digestion (DPSC-ED) 4,6,25 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be postulated that this cytokine is important for down-regulation of inflammatory and immune responses within PLs and for the repair of periapical bone loss. PL-MSCs, like other dental MSCs, also produce TGF-β (12,13). In our co-culture model, the number of PL-MSCs was significantly lower than the number of PL-ICs (1:10, respectively), therefore the contribution of TGF-β produced by PL-MSCs in the co-culture, could be considered as less important.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 70%
“…Except for their substantial differentiation capacity and low immunogenicity, it was demonstrated that different MSCs, including our PL-MSCs lines, have profound anti-proliferative and anti-inflammatory effects (9,12,13). Since the production of proinflammatory cytokines is controlled by the immunoregulatory cytokines, the principal aim of this study was to check the involvement of PL-MSCs in these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation